Smart Insular Grids: Opportunities and Challenges - Erdinc, Ozan; Catalao, Joao P. S.; Uzunoglu, Mehmet; Boynuegri, Ali Mat (IEEE, 2013)
The ever increasing environmental concerns together with depletion risk of conventional fossil fuels that can threat the energy independence of energy importing countries have led to more interest in renewable energy sources of locally produced energy. Increase in such sources together with new types of integrated loads has required new concepts to operate bulk electricity power grid. Accordingly, a relatively new concept - the smart grid - has been widely publicized recently with huge investments of both developed and developing country governments in this area. The smart grid concept is currently in the test phase and insular grids have been generally considered as one of the most suitable structures to evaluate the applicability of smart solutions. Thus, the general structure and applicable smart grid based strategies are presented in this study to promote the overall operating performance of such systems. The opportunities as well as the possible challenges of smart solutions are discussed, and the future requirements are evaluated.
Keywords: demand response; electric vehicles; energy storage; insular grids; renewable energy; smart grid; ENERGY; COMMITMENT; DESIGN; Energy & Fuels; Engineering